2021
DOI: 10.1002/smll.202006442
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Carbon Support: Few‐Layered Graphdiyne‐Decorated Carbon Nanotubes Capture Metal Clusters as Effective Metal‐Supported Catalysts

Abstract: Carbon‐supported metal nanocatalysts have received substantial attention for heterogeneous catalysis in industry. Hunting for suitable and impactful carbon supports that have strong interactions with metal nanocatalyst is a matter of great urgency. Herein, a well‐designed graphdiyne layer decorated on the carbon nanotubes sidewalls (CNT@GDY) serves as a novel carbon support. This unique hybrid structure effectively traps platinum and palladium atomic clusters (Pt/Pd‐ACs) with dimensions of 0.65 nm and 1.05 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 55 publications
(59 reference statements)
0
29
0
Order By: Relevance
“…Nevertheless, owing to the low conductivity of bulk GDY, the peak current significantly drops after modification with GDY (i.e., GDY/GCE). When compared to GDY/GCE, the peak current for GDY/G/GCE shows a significant improvement, proving that graphene can facilitate efficient electron transfer on the electrode surface and increase electrochemical activity. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, owing to the low conductivity of bulk GDY, the peak current significantly drops after modification with GDY (i.e., GDY/GCE). When compared to GDY/GCE, the peak current for GDY/G/GCE shows a significant improvement, proving that graphene can facilitate efficient electron transfer on the electrode surface and increase electrochemical activity. …”
Section: Resultsmentioning
confidence: 99%
“…21,43 (2) The unique pore structure of GDY allows heavy metal ions to be embedded, providing an ideal adsorption location. 26,31 As shown in Figure 3f, GDY/G/GCE also implements simultaneous detection of Pb 2+ and Cd 2+ . In the concentration range of 0.005−1.5 μM, the current response of GDY/G/GCE increases with the increase of Pb 2+ and Cd 2+ concentrations.…”
Section: Optimization Of Experimentalmentioning
confidence: 99%
“…Nowadays, the application of GDY-based materials in various electrochemical reactions, such as hydrogen evolution reaction(HER), oxygen evolution reaction(OER), ORR and over water splitting(OWS) have been widely investigated [68] . In those reactions, GDY can not only act as a support for the catalysts but also as metal-free catalysts by appropriate modifications [69,70] .…”
Section: Electrochemical Catalysismentioning
confidence: 99%
“…Therefore, because of their increased surface area and one-dimensional shape, TiO 2 are expected to be a feasible strategy, which offers an effective delocalization method for the charge carriers. Owing to many peculiar characteristics, such high charge-discharge capacity, excellent photocatalytic ability and high surface area, these one-dimensional nanostructures have been employed in electrochemical energy storage systems [17,18] in addition to in photovoltaics and semiconductor photocatalysts as well as catalysts support and gas sensors [19][20][21]. To produce one-dimensional nanostructures of TiO 2 (initially called needle-like structures), Kasuga et al revealed an alkali hydrothermal process [22].…”
Section: Introductionmentioning
confidence: 99%